Iconography of The Birth of the Virgin Mary on the Basis of a Homily of St. John Damascene - Salvador González, José María (Eikón / Imago, 2016)
As a consequence of the fact that the New Testament mentions few episodes and very few details of the real life of the Virgin Mary, among the Eastern Christian communities several apocryphal legends, that tried to supply this hermetic silence around the birth, infancy, youth, adulthood and death of the Mother of Jesus, arose during the first centuries of Christianity. These apocryphal accounts were then taken up and interpreted catechetically as a useful devotional matter by many Church Fathers, theologians and ecclesiastical writers. The reflections of these prestigious thinkers formed a solid corpus of doctrine, from which very important Marian devotions and liturgical feasts would soon follow. A primordial milestone in this “imaginary” life of Mary is her supernatural birth, after her miraculous conception in the bosom of her old and sterile mother Anne. As a natural fruit of these heterogenous literary and theological sources, from the tenth-eleventh centuries the medieval Byzantine and European artists approached with remarkable enthusiasm the iconographic theme of the Birth of the Virgin Mary as a significant episode of her life. On this basis, in this article we propose a triple complementary objective. First of all, after outlining the essential content of the apocryphal sources, we will broadly analyze the various theological theses that we believe are deductible from the emotional reflections that St. John Damascene expresses in a homily on the subject. Secondly, we will analyze some Byzantine and European paintings on the Birth of Mary, in order to determine to what extent the apocryphal accounts and the doctrinal statements of the Damascene are reflected in the characters, situations, attitudes, accessories and scenographic elements represented in these depictions. Finally, we will state some conclusions that we believe to be plausible in relating the Damascenian texts and the pictorial works of reference.